ANALISA BAURAN PEMASARAN (7P) UNTUK MENENTUKAN STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN (Studi Kasus Pada HomeIndustry CV Melati Kota Pangkalpinang) - Murtini, Afri; Zamhari; Oktalina, Gayatria (Jurnal Progresif Manajemen Bisnis, 2019)
This research was conducted to prove and verify whether the 7P Marketing Mix to Determine the Effect of Marketing Strategies in Increasing Sales Volume at Home Industry CV. Jasmine. Theories used in this research are management theory, marketing strategy theory, and sales volume theory. The method used in this research is descriptive quantitative approach with the aim to find the relationship between independent variables and dependent variables using statistical formulas that examine the relationship of products, prices, promotions, distribution channels, processes, participants and physical evidence affecting Sales Volume in Indusry Home CV . Jasmine. The statistical formula used to test hypotheses is Multiple Linear Regression Analysis. The sample in this study amounted to 100 people. Data processing techniques and data analysis from testing the hypothesis of this study. Hypothesis testing uses t-test and F-test with a significance level of 5%. This study also uses the coefficient of determination (R2) to determine the ability of independent variables to explain the dependent variable. The results of the simultaneous hypothesis test (F-test) show that the marketing mix of 7P to determine marketing strategies affects sales volume. The coefficient of determination (R2) is 0.797. It can be defined that 79.7% of the Sales Volume variable can be explained by the Marketing Mix (7p), while the remaining 20.3% is influenced by other variables not included in this study.The results of this study prove that there is a significant effect between products on sales volume. There is evidence that F arithmetic (2,420) table t table (1.98447). There is a significant effect between price and sales volume. This is proven by Fcount (4,032) table t table (1.98447). There is a significant influence between promotions on sales volume. This is proven by Fcount (8,281) table t table (1.98447). While Distribution Channels negatively affect sales volume. This is proven by Fcount (-2,864) table t table (1.98447). Participants have no effect on sales volume. This is evidenced by the value of Fcount (1,234) table t table (1.98447). there is a negative effect of the Process on sales volume. with F arithmetic (-2.163) ˂ t table (1.98447). Thus there is no effect of physical evidence on sales volume. Proven by Fcount 0.458) abeltable (1.98447)